Alcohol's harms to others in Wales, United Kingdom: Nature, magnitude and associations with mental well-being. (June 2019) - Quigg, Zara; Bellis, Mark A.; Grey, Hannah; Webster, Jane; Hughes, Karen
Abstract: Aim: To explore the nature and magnitude of alcohol's harms to others (AHTOs), and associations with mental well-being. Methods: Cross-sectional survey implemented amongst 891 randomly selected Welsh residents (aged 18+ years), via computer assisted telephone interviews. Questions established past 12-month experience of nine direct harms resulting from another person's alcohol consumption (e.g. violence) and five linked outcomes (e.g. concern for a child). The source (e.g. partner/stranger) and frequency of the AHTO were collected, and respondents' socio-demographics, drinking behaviours and mental well-being status. Results: During the past 12 months, 43.5% of respondents had experienced at least one direct harm (45.5% at least one direct harm/linked outcome). In demographically adjusted analyses, the odds of experiencing any direct harm decreased sequentially as age group increased (Adjusted Odds Ratio [AORs]: 1.9 [age 65–74 years] - 4.2 [age 18–34 years]), and was higher amongst binge drinkers (AOR, 1.5, p < 0.05). Associations between age group and suffering the direct harms anxiety, disrupted sleep, feeling threatened, property damage and emotional neglect were found. Experience of feeling threatened was lower amongst females (AOR 0.6, p < 0.05). In demographically adjusted analyses, low mental well-being was higher amongst those who had suffered alcohol-related financial issues (AOR 2.2, p < 0.001), emotional neglect (AOR 2.3, p < 0.01) and property damage (AOR 2.2, p < 0.05). Conclusion: AHTOs place a large, although unequal burden on adults in Wales. Individuals' drinking patterns are associated with experience of AHTOs. Critically, experience of some harms is associated with low mental well-being. Highlights: The harms from alcohol extend from the drinker to those around them (i.e. alcohol's harms to others [AHTOs]). AHTOs place a large, although unequal burden on the Welsh adult population, with young people and binge drinkers most at-risk. Experience of some AHTOs is associated with low mental well-being. AHTOs should be a consideration in the development, targeting and evaluation of alcohol policy and prevention activity.